Identification of genes associated with early and late response of methylmercury in human neuroblastoma cell line - Kim, Youn-Jung; Kim, Mi-Soon; Jeon, Hee-Kyung; Ryu, Jae-Chun (KOREAN SOC TOXICOGENOMICS & TOXICOPROTEOMICS, 2008)
Methylmercury (MeHg) is known to have devastating effects on the mammalian nervous system. In order to characterize the mechanism of MeHg-induced neurotoxicity, we investigated the analysis of transcriptional profiles on human 8k cDNA microarray by treatment of 1.4 mu M MeHg at 3, 12, 24 and 48 h in human neuroblastoma SH-SY5Y cell line. Some of the identified genes by MeHg treatment were significant at early time points (3 h), while that of others was at late time points (48 h). The early response genes that may represent those involved directly in the MeHg response included pantothenate kinase 3, a kinase (PRKA) anchor protein (yotiao) 9, neurotrophic tyrosine kinase, receptor, type 2 gene, associated with NMDA receptor activity regulation or perturbations of central nervous system homeostasis. Also, when SH-SY5Y cells were subjected to a longer exposure (48 h), a relative increase was noted in a gene, glutamine-fructose-6-phosphate transaminase 1, reported that overexpression of this gene may lead to the increased resistance to MeHg. To confirm the alteration of these genes in cultured neurons, we then applied real time-RT PCR with SYBR green. Thus, this result suggests that a neurotoxic effect of the MeHg might be ascribed that MeHg alters neuronal receptor regulation or homeostasis of neuronal cells in the early phase. However, in the late phase, it protects cells from neurotoxic effects of MeHg.
Keywords: SELENOPROTEIN-W; SACCHAROMYCES-CEREVISIAE; TARGET; BRAIN; GLUTATHIONE; RECEPTOR; BINDING; PROTEIN; METALS; YOTIAO